2008
DOI: 10.5194/acpd-8-9263-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do atmospheric aerosols form glasses?

Abstract: Abstract. A new process is presented by which water-soluble organics might influence ice nucleation, ice growth, chemical reactions and water uptake of aerosols in the upper troposphere: the formation of glassy aerosol particles. Glasses are disordered amorphous (non-crystalline) solids that form when a liquid is cooled without crystallization until the viscosity increases exponentially and molecular diffusion practically ceases. The glass transition temperatures, Tg, homogeneous ice nucleation temperatures, T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(173 citation statements)
references
References 80 publications
8
164
1
Order By: Relevance
“…One possible mechanism for the enhancement in γ with increasing RH is that the particle's liquid water content controls particle phase state and the rate of OH loss. Previous studies indicate that LEV constitutes a highly viscous (glassy) solid or semisolid amorphous phase state under dry conditions [ Zobrist et al , ; Mikhailov et al , ]. However, LEV aerosol particles undergo a humidity‐induced phase transformation to less viscous, i.e., semisolid or liquid‐like, particles at RH = 30–60% [ Mikhailov et al , ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible mechanism for the enhancement in γ with increasing RH is that the particle's liquid water content controls particle phase state and the rate of OH loss. Previous studies indicate that LEV constitutes a highly viscous (glassy) solid or semisolid amorphous phase state under dry conditions [ Zobrist et al , ; Mikhailov et al , ]. However, LEV aerosol particles undergo a humidity‐induced phase transformation to less viscous, i.e., semisolid or liquid‐like, particles at RH = 30–60% [ Mikhailov et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that OH can react not only on the surface of amorphous LEV particles but also within the particle bulk at higher RH. LEV represents just one of many types of amorphous organic material, which also include carbohydrates, proteins, carboxylic acids, SOA, and humic‐like substances [ Shiraiwa et al , ; Mikhailov et al , ; Zobrist et al , ; Murray , ; Wang et al , ]. Thus, consideration of OH reactivity with other amorphous organic substances will further improve our understanding of its influence on chemical aging and thus atmospheric chemistry and climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These large ice crystals are suggested to have grown on particles that acted as ice nuclei at low supersaturations with respect to ice (Jensen et al 2008). Very recently, Zobrist et al (2008) based on laboratory experiments showed that mixed organic/inorganic aerosols may form glasses at temperatures prevalent in the upper troposphere, and that this may greatly reduce their uptake of water and hence their homogeneous ice formation ability.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The organic-rich phase of atmospheric aerosols can be classified as a liquid ( < 10 2 Pa·s; where is the dynamic viscosity), a semi-solid (10 2 Pa·s < <10 12 Pa·s) or a solid ( > 10 12 Pa·s), depending on ambient conditions and chemical composition. [22][23][24][25] Indeed, Virtanen et al showed that secondary organic aerosol (SOA) could exist in a glassy phase, while other studies suggest that aerosol particles could be characterised as gels or rubbers. [26][27][28][29] Based on the relationship between viscosity and diffusion constant suggested by the Stokes-Einstein equation, it might be expected that diffusion constants could be characterised by a similarly wide range, depending on the viscosity and phase of the aerosol.…”
Section: Introductionmentioning
confidence: 99%